2006
DOI: 10.1136/jcp.2006.037333
|View full text |Cite
|
Sign up to set email alerts
|

Ep-CAM expression in pancreatic and ampullary carcinomas: frequency and prognostic relevance

Abstract: Ep-CAM overexpression was detectable in the majority of cases with pancreatic and ampullary cancer. Therefore, Ep-CAM represents an attractive target for immune-based therapeutic interventions in these tumour entities. However, the prognostic value of Ep-CAM overexpression remains undetermined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
78
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(83 citation statements)
references
References 24 publications
3
78
0
2
Order By: Relevance
“…Efforts for standardising the immunohistochemical staining and evaluation procedure were explained highlighting an advanced scoring system that reflected both frequency, and intensity of staining. A similar negative correlation between EpCAM expression and survival as previously observed by the group for breast and gall bladder cancer (Varga et al, 2004) was also now observed with ampullary carcinoma of the pancreas (Fong et al, 2006) and for squamous cell cancer of head and neck. N Stoecklein (Duesseldorf, Germany) reported a negative correlation between EpCAM expression and overall survival in patients with squamous cell carcinoma of the oesophagus, a very deadly disease with no established systemic treatment option.…”
Section: Epcam Expression and Survival Prognosis Of Cancer Patientssupporting
confidence: 84%
“…Efforts for standardising the immunohistochemical staining and evaluation procedure were explained highlighting an advanced scoring system that reflected both frequency, and intensity of staining. A similar negative correlation between EpCAM expression and survival as previously observed by the group for breast and gall bladder cancer (Varga et al, 2004) was also now observed with ampullary carcinoma of the pancreas (Fong et al, 2006) and for squamous cell cancer of head and neck. N Stoecklein (Duesseldorf, Germany) reported a negative correlation between EpCAM expression and overall survival in patients with squamous cell carcinoma of the oesophagus, a very deadly disease with no established systemic treatment option.…”
Section: Epcam Expression and Survival Prognosis Of Cancer Patientssupporting
confidence: 84%
“…To our knowledge, there was only one report regarding the relationship between Ep-CAM expression and the prognosis of pancreatic cancer patients (Fong et al, 2008). According to their opinion, no significant difference was shown in the prognosis between the highand low-Ep-CAM expression in all 153 patients, but in the subgroups of patients with advanced disease, highEp-CAM expression group showed significantly poor prognosis compared with low expression.…”
Section: Discussionmentioning
confidence: 91%
“…In this study, we divided enrolled patients into Ep-CAM high and low-expression group by four of Ep-CAM expression scoring and this cut-off line was based on the previous reports (Gastl et al, 2000;Varga et al, 2004;Fong et al, 2008;Noda et al, 2009). However, as shown in Figure 2, it might not be appropriate to set the cut-off line at four because there were many patients scoring between 4 and 6.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We recently showed that EpCAM (TROP1, GA733-2) overexpression predicts poor survival in different cancer entities. [14][15][16] Interestingly, expression of TROP2 did not correlate with EpCAM expression. 17 Anti-EpCAM antibodies can cause significant reduction in mortality and relapse rates of resected colon cancer patients following treatment with the EpCAM-specific monoclonal antibody edrecolomab.…”
Section: Discussionmentioning
confidence: 96%